Pengembangan Bahan Pembelajaran Multimedia Penjasorkes untuk Meningkatkan Budaya Hidup Sehat pada Siswa Kelas VIII MTsN Aryojeding Tulungagung - Yulianto, Eko (Universitas Nusantara PGRI Kediri, 2023)
This study aims to produce due to the limited knowledge of teachers and the development of learning multimedia for grade VIII students of SMP/MTs a culture of healthy living (NAPZA/Narcotics) materials. This research is a development research conducted through several stages, namely as follows: introduction, development of learning designs, developing initial products, and product evaluation. After going through the production stage, an initial product is produced which is validated by material experts and media experts. Furthermore, the product was tested on students through large group trials. The subjects of the product trial were 15 class VIII students at MTs Negeri Aryojeding. Data is collected through a questionnaire. Data in the form of research results regarding product quality, suggestions for product improvement. Qualitative data were analyzed with descriptive statistics. Based on the results of research data in the form of questionnaires from multimedia learning that has been tested. The results of the validation of material experts were